A review: Rational design of catalysts for catalytic decomposition of ammonia - Medina, Elvis; Fernández, Camila; Karelovic, Alejandro; Jiménez, Romel (International journal of hydrogen energy, 2024)
The growth of the hydrogen (H2) economy, which is considered by many to be the future energy vector, is partially limited by the development of techno-economically viable alternatives for its storage and transport. Although the use of ammonia (NH3) as a H2 carrier represents an attractive alternative owing to its high H2 content (17.8% w/w), availability of infrastructure for easy handling, COx-free product stream, and feasibility of more efficient transport, among others, some challenges must be solved for its consolidation. In particular, for the conversion of ammonia back into hydrogen, great scientific effort has been devoted to the synthesis of efficient catalytic systems with low environmental impact and associated costs, as an alternative to the expensive and scarce ruthenium-based catalysts, the most active ones for the decomposition of ammonia. Although non-noble metals such as Co, Ni, and Mo have been fully identified as moderately active compounds in the decomposition of NH3, the potential of their use still needs to be looked at in greater depth, notedly the alloys of these transition metals. Theoretical DFT calculations have revealed synergy between the compositional ratio of metals present in the catalyst and the binding energy of nitrogen adatoms on the metallic surface (volcano shape), which is the main activity descriptor and pointed out, from a mechanistic point of view, as the kinetically relevant step (RDS) frequently reported in the literature. In general, given the relationship between the activity descriptor and the Turnover Frequency (TOF), transition state calculations reveal that certain stoichiometries, with different crystal structures of the originating metals, present higher or lower catalytic activity during the catalytic decomposition of ammonia. This review brings together the significant knowledge acquired in the recent years on the design and rational evaluation of bimetallic catalysts for the catalytic decomposition of ammonia, providing a useful reference framework for future research and innovation in this area. •The RDS and MARI are the recombination desorption of adatoms of Nitrogen and N∗.•Co–Mo bimetallic catalyst is the most studied, showing DFT - experimental synergy.•Nanoparticle's stoichiometry and coordination number are fundamental variables.•Synthesis, pre-treatment, and activation methods are means to modify the former.•We recommend LHHW model for its physical validation of fitted kinetic parameters.